Pengaruh Pemberian Puding Buah Naga Merah (Hylocereus Polyrhizus) Terhadap Kadar Kolesterol Total Pasien Hiperkolesterolemia Rawat Jalan Di RSUD Kota Mataram - Sarafatayat Sarafatayat; Fifi Luthfiyah; Susilo Wirawan; Ni Ketut Sri Sulendri (Jurnal Gizi Prima (Prime Nutrition Journal), 2018)
Background. Hypercholesterolemia is a condition of cholesterol levels increased in the blood. Hypercholesterolemia can cause atherosclerosis. Atherosclerosis can cause various cardiovascular diseases such as coronary heart disease and stroke.Research Methods. This type of research is using quasi-experimental study with pretest and posttest with control group design. The sample was given 150 g of red dragon fruit pudding every day for 14 days. Data obtained from this study were analyzed using paired test and independent t-test.Research Result. The average total cholesterol level of control group before the research was 290.20 mg / dL while the cholesterol level of intervention group before the research was 290.30 mg / dL. The average total cholesterol level of the control group after intervention was 289.0 mg / dL while the total cholesterol level of the intervention group was 234.20 mg / dL. The reduction in the total cholesterol level of the intervention group was 56.10 mg / dL.Conclusion. Red dragon fruit pudding affects the decrease of total cholesterol levels.